2020
DOI: 10.1101/2020.05.28.20097402
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disinfection of N95 Respirators with Ozone

Abstract: The coronavirus disease 2019 crisis is creating a shortage of personal protective equipment (PPE), most critically, N95 respirators for healthcare personnel. Our group was interested in the feasibility of ozone disinfection of N95 respirators as an alternative for healthcare professionals and organizations that might not have access to other disinfection devices. We tested the effectiveness of ozone on killing Pseudomonas aeruginosa (PsA) on three different N95 respirators: 3M 1860, 3M 1870, and 3M 8000. We us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Overall, 16 studies measured disinfection and durability 12, 15, 19, 20, 22, 27-30, 33, 36, 47, 49, 51, 62, 64 , 16 studies measured only disinfection 13, 18, 23, 24, 31, 38, 40, 41, 43, 44, 48, 56, 63, 65-67 and 26 studies measured only durability 7, 14, 16, 17, 21, 25, 26, 32, 34, 35, 37, 39, 42, 45, 46, 50, 52-55, 57-61, 68 . Thus, 32 studies measured disinfection and 42 measured durability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 16 studies measured disinfection and durability 12, 15, 19, 20, 22, 27-30, 33, 36, 47, 49, 51, 62, 64 , 16 studies measured only disinfection 13, 18, 23, 24, 31, 38, 40, 41, 43, 44, 48, 56, 63, 65-67 and 26 studies measured only durability 7, 14, 16, 17, 21, 25, 26, 32, 34, 35, 37, 39, 42, 45, 46, 50, 52-55, 57-61, 68 . Thus, 32 studies measured disinfection and 42 measured durability.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 159 individual mask reuse tests were conducted in 42 studies 7, 12, 14-17, 19-22, 25-30, 32-37, 39, 42, 45-47, 49-55, 57-62, 64, 68 . The masks tested included: 114 tests with N95s (72%), an additional four tests with KN95s (2.5%), seven tests with folded or molded or HKYZ N95s (4.4%), four tests with FFPs (2.5%), and two tests with respirator fabric (1%).…”
Section: Resultsmentioning
confidence: 99%
“…Much of the work to date has focused on sterilization of respirators for subsequent reuse. While a few studies have been completed and submitted to preprint servers after waiting for data from extant labs [24][25][26][27][28][29], a number of other preprints [30,31] and publications [32][33][34] have developed apparatuses to measure filtration efficiency as best they can independently. There is significant heterogeneity in these setups; some are built with assistance from labs which study aerosols, others with equipment found on hand.…”
Section: Introductionmentioning
confidence: 99%
“…In an initial report, ozone was used to inactivate Pseudomonas aeruginosa on multiple N95 models with no significant change in filtration for up to 10 cycles. 109 Further study is required to establish its promise for FFR.…”
Section: Ffr Decontaminationmentioning
confidence: 99%